Pigs in heaven - Kingsolver, Barbara (London : Faber and Faber, 1993)
Six-year-old Turtle Green witness a freak accident drawing her and her mother into a conflict of historic proportins.
Keywords: Adopted children -- Fiction; Cherokee -- daughter relationship -- Fiction; Mothers and daughters -- Fiction